DISTRIBUTION AND PECULIARITIES OF DOG TRICHURIASIS COURSE ON THE TERRITORY OF THE TOWN OF POLTAVA - Borodai, Ye. O.; Godyna, V. P. (Scientific Progress & Innovations, 2019)
Today, dog breeding is of great importance worldwide in various sectors of the economy. The need in de-veloping utility, hunting, sports, and decorative dog breeding is growing as these animals are indispensable human assistants. Helminthic diseases, caused by a large group of parasitic organisms belonging to the Nematoda type, are extremely dangerous for carnivorous animals. Researchers point out to the considerable spreading of the digestive tract nematodoses among the population of the domestic dog (Canis lupus famil-iaris); trichuriasis occupies one of the leading places among such diseases. The research was conducted in the Laboratory of the Department of parasitology and veterinary-sanitary expert examination of Poltava State Agrarian Academy. The purpose of the study was to investigate the distribution and peculiarities of dog trichuriasis in Poltava. According to the results of coproscopic examination of dogs, it was found that the average prevalence of the trichuriasis invasion in the town of Poltava was 25.93 %. The invasiveness indices of animals with Trichuris vulpis depended on their age. Young dogs aged from 6 to 12 months were the most affected – the prevalence of infection reached 39.02 %. Subsequently, with the aging of dogs, the prevalence gradually decreased to 14.29% – in dogs older than 6 years. Puppies under the age of 6 months were the least infested with trichuriasis pathogen, the prevalence of infection in this case was only 8.57 %. The pecu-liarities of the breed susceptibility of dogs to the pathogen of trichuriasis were characterized by the highest indices of infection prevalence in dogs of the French bulldog (72.73 %) and Pekingese breeds (40.00 %). Less frequently, trichuriasis was diagnosed in Labrador-Retriever dogs, poodles, and Central Asian shep-herd dogs. The infection prevalence indices ranged from 12.50 to 16.67 %. It has been found that trichuria-sis occurs in the form of mono-invasion in 53.57 % of cases and in 46.43% – in the form of mixed invasions. Three species of nematodes parasitizing in the intestines of dogs were the associates of mixed invasions. Two-component mixed invasions were represented by T. vulpis and Uncinaria stenocephala (38.47 %), T. vulpis and Toxascaris leonina (30.77 %), T. vulpis and Toxocara canis (15.38 %). Three-component mixed invasion was revealed in 15.38 % of the diseased dogs and it was represented by T. vulpis, U. stenocephala, and T. leonina. Most often, trichuriasis was registered in association with uncinariosis (53.85 %) and toxascarosis (46.15 %). The association of trichurises and toxocares (15.38 %) was less fre-quently diagnosed.